2012
DOI: 10.1007/s10439-012-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Connections Between Risk Factors of Intracranial Aneurysms: A Review

Abstract: The purpose of this article is to review studies of aneurysm risk factors and the suggested hypotheses that connect the different risk factors and the underlying mechanisms governing the aneurysm natural history. The result of this work suggests that at the center of aneurysm evolution there is a cycle of wall degeneration and weakening in response to changing hemodynamic loading and biomechanic stress. This progressive wall degradation drives the geometrical evolution of the aneurysm until it stabilizes or ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 141 publications
(182 reference statements)
4
74
0
Order By: Relevance
“…42,43 Certainly, variations in hemodynamics and different risk factors among different individuals contribute to the heterogeneity of the disease.…”
Section: Relationship Between Hemodynamics and Aneurysm Developmentmentioning
confidence: 99%
“…42,43 Certainly, variations in hemodynamics and different risk factors among different individuals contribute to the heterogeneity of the disease.…”
Section: Relationship Between Hemodynamics and Aneurysm Developmentmentioning
confidence: 99%
“…A variety of genes or chromosomal regions have been identified in both familial and sporadic cases of IAs. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] In linkage studies, regions on chromosomes 1p34.3-p36.13, 7q11, 19q13.3, and Xp22 have been associated with IAs. Genome-wide association studies identified replicated associations on chromosome 4q31.23 (EDNRA), 8q12.1 (SOX17), 9p213 (CDKN2A/CDKN2B/CDKN2BAS), 10q24.32 (CNNM2), 12q22, 13q13.1 (KL/STARD13), 18q11.2 (RBBP8), and 20p12.1, with the strongest evidence for the CDKN2BAS and SOX17 genes.…”
Section: Family History and Geneticsmentioning
confidence: 99%
“…While aneurysms can remain unsymptomatic for years, they may grow and eventually rupture, which is often lethal [1,2]. The formation and subsequent growth of an aneurysm is not only caused by systemic risk factors, but a significant role is also attributed to the local haemodynamic environment [3]. Blood flow patterns cause a nonuniform mechanical load on the vessel wall which may lead to deleterious remodelling [4 -6].…”
Section: Introductionmentioning
confidence: 99%